Different lepidopteran elicitors account for cross-talk in herbivory-induced phytohormone signaling - Diezel, Celia; Gaquerel, Emmanuel (Plant physiology, 2009)
Salicylic acid (SA), jasmonic acid (JA), ethylene (ET), and their interactions mediate plant responses to pathogen and herbivore attack. JA-SA and JA-ET cross-signaling are well studied, but little is known about SA-ET cross-signaling in plant-herbivore interactions. When the specialist herbivore tobacco hornworm (Manduca sexta) attacks Nicotiana attenuata, rapid and transient JA and ET bursts are elicited without significantly altering wound-induced SA levels. In contrast, attack from the generalist beet armyworm (Spodoptera exigua) results in comparatively lower JA and ET bursts, but amplified SA bursts. These phytohormone responses are mimicked when the species' larval oral secretions (OSSe and OSMs) are added to puncture wounds. Fatty acid-amino acid conjugates elicit the JA and ET bursts, but not the SA burst. OSSe had enhanced glucose oxidase activity (but not β-glucosidase activity), which was sufficient to elicit the SA burst and attenuate the JA and ET levels. It is known that SA antagonizes JA; glucose oxidase activity and associated hydrogen peroxide also antagonizes the ET burst. We examined the OSMs-elicited SA burst in plants impaired in their ability to elicit JA (antisense [as]-lox3) and ET (inverted repeat [ir]-aco) bursts and perceive ET (35s-etr1b) after fatty acid-amino acid conjugate elicitation, which revealed that both ET and JA bursts antagonize the SA burst. Treating wild-type plants with ethephone and 1-methylcyclopropane confirmed these results and demonstrated the central role of the ET burst in suppressing the OSMs-elicited SA burst. By suppressing the SA burst, the ET burst likely facilitates unfettered JA-mediated defense activation in response to herbivores that otherwise would elicit SA.